Inhibition of CD83 Alleviates Systemic Inflammation in Herpes Simplex Virus Type 1-Induced Behçet's Disease Model Mouse - S. M. Shamsul Islam; Hae-Ok Byun; Bunsoon Choi; Seonghyang Sohn (Hindawi Limited, 2019)
Behçet's disease (BD) is an autoinflammatory disease that can lead to life- and sight-threating complications. Dendritic cells (DCs) are the most potent antigen-presenting cells that can regulate multiple inflammatory pathways. The objective of this study was to investigate the association of the DC stimulatory molecule CD83 with BD. Frequencies of costimulatory molecules expressing DCs in peripheral blood leukocytes (PBL) were measured by flow cytometry (FACS). The severity of symptoms in HSV-1-induced BD symptomatic mice was also assessed. Frequencies of CD83-positive cells were significantly increased in mice exhibiting BD symptoms, compared to those in asymptomatic mice. Abatacept, a CD80/86 blocker, significantly decreased the frequencies of CD83-positive cells in a time- and dose-dependent manner. BD symptomatic mice treated with Abatacept showed gradual reduction in the severity score of symptoms. Intraperitoneal injection of CD83 siRNA significantly reduced the frequencies of CD83-positive cells in PBL and peritoneal macrophages. After CD83 siRNA injection, BD symptoms of mice were improved and disease severity was decreased. Discontinuation of CD83 siRNA deteriorated symptoms while readministration of CD83 siRNA again improved BD symptoms of mice. These results clearly indicate the involvement of CD83-expressing cells in the inflammatory symptoms of BD. Therefore, CD83 might be useful as a therapeutic target for BD.